Are body dysmorphic symptoms dimensional or categorical in nature? A taxometric investigation in adolescents. (November 2021) - Bala, Manya; Quinn, Rachel; Jassi, Amita; Monzani, Benedetta; Krebs, Georgina
Highlights: The latent structure of body dysmorphic symptoms in adolescents was examined. Taxometric analyses indicated a dimensional structure for body dysmorphic symptoms. Results suggest that BDD may represent an extreme end of a symptom continuum. Findings support dimensional approaches for clinical assessment of BDD symptoms. Findings support the use of analogue (i.e. non-clinical) samples in BDD research. Abstract: Body dysmorphic disorder (BDD) is a debilitating mental health condition which usually emerges during adolescence and is characterised by distressing and impairing appearance concerns. It is currently unclear whether body dysmorphic concerns represent an extreme manifestation of normal appearance concerns (a dimensional conceptualisation), or whether they are qualitatively distinct (a categorical conceptualisation). This study aimed to determine whether body dysmorphic symptoms are dimensional or categorical in nature by investigating the latent structure using taxometric procedures. Body dysmorphic symptoms were assessed using validated measures among 11-16-year-old school pupils ( N =707). Items of the Body Image Questionnaire Child and Adolescent version were used to construct four indicators that broadly corresponded to the DSM-5 diagnostic criteria for BDD (appearance concerns, repetitive behaviours, impairment, and insight). Indicators were submitted to three non-redundant taxometric procedures (MAMBAC, MAXEIG and L-MODE). Overall, results of all three taxometric procedures indicated a dimensional latent structure of body dysmorphic symptoms. The current study provides preliminary evidence that body dysmorphic symptoms are continuously distributed among adolescents, with no evidence of qualitative differences between mild and severe symptoms. Implications for clinical practice and research are discussed.